Glaciers and ice caps - Bramwell, Martyn (London ; New York : F. Watts, 1986)
Describes the formation, structure, and movement of glaciers, ice caps, and ice sheets and their effects on the earth's surface.
Includes index.
School Library Journal.
Book Links (A.L.A.).
6.4
5-8
Keywords: Glaciers -- Juvenile literature; Ice caps -- Juvenile literature; Glaciers; Glaciers; Glaciers; Ice caps